Effectiveness of Urea Crystallization Method in the Producting Omega-3 Concentrate from Tuna (Thunnus sp.) - Sugeng Heri Suseno; Dhanurendra Izza Dewangga; Purnama Arafah; Rizfi Fariz Pari (Institut Pertanian Bogor, 2026)
Omega-3 concentrates developed from fish oil without any other components are excellent for overall health. The objective of this study was to evaluate the effectiveness of the urea crystallization method in relation to the iodine value and the increase in total omega-3 fatty acids during the production of omega-3 concentrates from tuna fish oil using response surface methodology (RSM). Using the urea crystallization method, pure ethyl ester oil is mixed with urea, then left to stand at a low temperature with predetermined ratios and times to obtain omega-3 concentrate. The total omega-3 content in the crude tuna oil obtained in this study was 19.51%. The total omega-3 content from pure tuna oil was 32.90%. Meanwhile, the total omega-3 content in the tuna omega-3 concentrate was 16.97%. Longer storage times were found to reduce saturated fat content and increase omega-3 levels, as indicated by higher iodine values. Keywords: low-temperature crystallization, omega-3 concentrate, response surface methodology. tuna oil